Pendampingan Penyusunan Modul Ajar Secara Small Group Discussion Pada Tahapan Plan Lesson Study - Widayanto Wido Yanto (Inovasi-Jurnal Diklat Keagamaan, 2022)
Lesson study is a learning activity carried out by a group of teachers and education experts which includes 3 (three) steps of activity, namely planning (plan), implementation of learning (do) and observation followed by reflection (see) on a planning and implementation of learning. FGD means systematic activities of collecting data and information about a specific problem related to constructing teaching module through group discussion. This descriptive qualitative study aims to describe the effectiveness of FGDs in constructing teaching module to meet the implementation of the 2022 curriculum or Kurikulum Merdeka (Kurmer) through lesson study. The finding said that the lesson study participants were able to construct teaching module well. It was concluded that FGDs assistance were effective in constructing teaching module through lesson study.